PENGUJIAN KEMAMPUAN ANTAGONISTIK KHAMIR Rhodotorula spp. ASAL KEBUN RAYA CIBODAS TERHADAP KAPANG DARI TANAMAN TOMAT TERINFEKSI DENGAN CO-CULTURE - Anggita R Hafsari; Ariyanti Oetari; Andi Salamah; Wellyzar Sjamsuridzal (JURNAL ISTEK, 2011)
Aspergilus ochraceu and A. terreus had been known as mould that causes significant loss to quality of tomatoes. One of potential methods to control the development of this mould by using the antagonistic activity of Rhodotorula sp. Six strains of Rhodotorula sp., UICC Y-318, UICC Y-325, UICC Y- 332, UICC Y-381, UICC Y-384, and UICC Y-386, which isolated from Cibodas Botanical Garden, West Java were observed for its antagonistic activity against mould A. ochraceu D1.2.2.2.SSM3 and A. terreus D2.2.MC. Co-culture method was used as 1.58 to 5.59 x 108 CFU/ml Rhodotorula sp. growth together with 7 x 107 CFU/ml A. ochraceus D1.2.2.2.SSM3 and 7.5 x 107 CFU/ml A. terreus D2.2.MC at PDB. Result showed that the highest percentage reduction of conidial heads and hyphal width was show by Rhodotorula sp. UICC Y-318 against A.ochraceus (9.45% and 12.43%; 7.10% and 7.51%, 2 and 3 day after incubation, respectively).